HISTORITAS PERKEMBANGAN HADIS (DARI PERIODE KLASIK HINGGA KONTEMPORER) - Junaid bin Junaid; Muh. Nasruddin A (CARITA: Jurnal Sejarah dan Budaya, 2024)
ABSTRACT The history of the study of hadith from time to time experienced a very significant development, initially the study of hadith from oral to oral developed into writing, the change was nothing but a form of concern for the loss of the Prophet's traditions, the development of hadith reached its peak when entering the tabiin period precisely the reign of Caliph Umar bin Abdul Aziz, where hadith at this time was officially codified in order to overcome the spread of false traditions pioneered by the perpetrators of heresy. Furthermore, after the hadith was codified its development became very rapid, with the birth of canonical books of hadith until the emergence of terms of hadith scholarship that were oriented as hadith selectors (sanad criticism of hadith) and hadith sharh books appeared as explanations of the Prophet's traditions. Until the next period, the study of hadith shifted not only to sanad criticism but has entered criticism of the matan. Even along with the times that have entered the digital era, hadith began to be packaged in order to present the study of hadith more easily. ABSTRAK Sejarah kajian hadis dari masa ke masa mengalamai perkembangan yang sangat signifikan, mulanya kajian hadis dari lisan ke lisan berkembang menjadi tulisan, perubahan tersebut tak lain sebagai bentuk kekhawatiran akan hilangnya hadis-hadis Nabi SAW, perkembangan hadis mencapai puncaknya ketika memasuki periode tabiin tepatnya pemerintahan khalifah Umar bin Abdul Aziz, dimana hadis pada masa ini resmi dikodifikasi guna menanggulangi tersebarnya hadis-hadis palsu yang di pelopori oleh para pelaku bid’ah. Lebih lanjut, setelah hadis dikodifikasi perkembanganya menjadi sangat pesat, dengan lahirnya kitab-kitab kanonik hadis hingga muncul term-term keilmuan hadis yang berorientasi sebagai penyeleksi hadis (kritik sanad hadis) serta muncul pula kitab-kitab syarh hadis sebagai penjelas hadis-hadis Nabi SAW. Hingga periode selanjutnya kajian hadis beralih tidak hanya berkutat pada kritik sanad melainkan sudah memasuki kritik terhadap matan. Bahkan seiring dengan perkembangan zaman yang sudah memasuki era digital, hadis mulai di kemas di dalamnya guna menghadirkan pengkajian hadis dengan lebih mudah.